Robô humano: estudo sobre humanização no atendimento com chatbot - Rebecchi, Adriana de Barros (2020)
This study addresses how the influence of the persona helps in the humanization of chatbots and seeks to evaluate/measure its impacts in terms of satisfaction with the service provided to the client, based on perceived usefulness and ease of use,. The theoretical review includes definitions of artificial intelligence, customer service with the chatbot tool, and humanization with virtual assistants. As a method, we chose to develop a quantitative analysis of a database of calls performed by chatbot from the institution SEBRAE-SP, through a survey with 153 clients who used this tool. We tested the following hypotheses: H1 - Perceived utility in the experience with a chatbot directly impacts the satisfaction index. H2 – Perceived ease of use in the experience with a chatbot directly impacts the satisfaction index. H3 – The need for human interaction has a moderating effect on the impact of perceived utility on the satisfaction index. H4 - The need for human interaction has a moderating effect on the impact of perceived ease of use on the satisfaction index. The results proved that perceived usefulness and ease of use directly impact the satisfaction index, considering that humanization of the chatbot is very important to increase this index. This study brings insights to companies seeking to improve their service with this type of technology, supplying better customer experience, and respecting the company's strategy.